2012
DOI: 10.1007/s00277-011-1403-0
|View full text |Cite
|
Sign up to set email alerts
|

Unstable hemoglobin Rush [beta 101(G3) Glu>Gln, HBB:c.304G>C] in a Brazilian family with moderate hemolytic anemia

Abstract: Hemoglobin Rush is an unstable variant generated by a mutation of the β-globin gene which causes amino acid replacement Glu>Gln in the central cavity of hemoglobin (G3). Many members of a Brazilian family of Italian descent have hemoglobin Rush. This is the second report in world literature. Clinical and laboratory features were retrieved and gene mutation was characterized. Hemoglobin electrophoresis, gene sequencing, and restriction fragment length polymorphism with Hpy188I were used to characterize it. In 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…However, the migration of the Hb Rush faction is very similar to that of Hb F on these electrophoreses. As shown in our results, Hb Rush is distinguishable from Hb F on gel electrophoresis (Figure 2A), thus potentially confounding diagnosis [4,5]. Our findings revealed the capillary electrophoresis pattern of Hb Rush, which showed clearly separation of Hb Rush from the Hb F fraction (Figure 2B).…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…However, the migration of the Hb Rush faction is very similar to that of Hb F on these electrophoreses. As shown in our results, Hb Rush is distinguishable from Hb F on gel electrophoresis (Figure 2A), thus potentially confounding diagnosis [4,5]. Our findings revealed the capillary electrophoresis pattern of Hb Rush, which showed clearly separation of Hb Rush from the Hb F fraction (Figure 2B).…”
Section: Discussionsupporting
confidence: 61%
“…Therefore, our findings do not exclude the possibility that the unstable Hb Rush variant might have arisen more than once in Chinese populations. The Chinese families in this study and the two previously reported families of African and European origins exhibited wide geographical isolation and significant race differences [4,5]. Therefore, we propose that the Hb Rush variant has experienced multiple independent origins worldwide.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations